Managing AIDS stigma - William L. Holzemer; Leana R. Uys (Taylor & Francis Group, 2004)
According to anecdotal reports, AIDS stigma and discrimination continue to influence people living with and affected by HIV disease as well as their health care providers, particularly in southern Africa where the burden of AIDS is so significant. Stigma is perceived as a major limiting factor in primary and secondary HIV/AIDS prevention and care. It reportedly interferes with voluntary testing and counselling, and with accessing care and treatments, thereby increasing suffering and shortening lives. Many health care workers in southern Africa have come to the conclusion that unless stigma is conquered, the illness will not be defeated. While there is substantial anecdotal evidence of the impact of stigma on AIDS care, very little rigorous research has been conducted. This article explores three questions: What is AIDS stigma? What is the impact of AIDS stigma? How can health care providers help to manage AIDS stigma?